Analisis Hukum Pidana Terkait Fungsi dan Permasalahan Lembaga Pemasyarakatan Kelas IIA Ambon - Dita Sri Wahyuningsih Antula; M Alpi Syahrin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study is entitled "Criminal Law Analysis Related to the Functions and Problems of Class IIA Ambon Penitentiary". Class IIA Ambon Penitentiary plays an important role in the criminal justice system in Indonesia, especially in restoring and reintegrating prisoners' social life. However, this prison faces several problems, namely overcapacity, acts of violence, and human rights violations that interfere with the effectiveness of guidance. This study is directed to analyze the role of Class IIA Ambon Penitentiary in the context of criminal law and identify the obstacles experienced in its implementation. This study uses normative legal research with a qualitative approach. Normative legal research is applied because this study discusses the analysis of legal aspects related to Class IIA Ambon Penitentiary, namely laws and regulations, legal principles, and legal implementation practices. A qualitative approach is used to better understand legal phenomena through interpretation of secondary data, such as literature, journals, books, and laws and regulations. From this analysis, it is recommended that related parties increase supervision and policy reform at Class IIA Ambon Penitentiary to support rehabilitation goals and ensure the protection of prisoners' rights. This research is expected to contribute to the development of a better correctional system in Indonesia.